2016
DOI: 10.1080/1369118x.2016.1142594
|View full text |Cite
|
Sign up to set email alerts
|

Rating the revolution: Silicon Valley in normative perspective

Abstract: Silicon Valley, California, home of Apple, Facebook, Twitter, Google, etc, is widely regarded as the epicentre of the information revolution. However, it is not just a technical or economic phenomenon; it has also made a social revolution. The article evaluates Silicon Valley from a normative perspective, seeking to identify its real societal impact, negative as well as positive. A select review of significant literature is followed by exposition of primary data, based on in situ face-to-face interviews with V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…Such myths, signs of usurpation, hide a domination that generates oligarchic power structures, poverty of imagination, decline of poetic sensibility, conversation and empathy, shallow obsession with digital gadgets, in sum, knowledge aversion (cf. Aschoff, 2018;Collin and Pedersen, 2015;Duff, 2016). What follows from this line of argumentation is that the task of a renewed hermeneutic social theory is twofold: to criticize and negate the anti-intellectual structures and corresponding knowledge-averse culture of the digital age; and to cultivate the poetic sensibility and and intellectual capacity to face an open universe and imagine one beyond usurpation of dominating value spheres.…”
Section: Discussionmentioning
confidence: 99%
“…Such myths, signs of usurpation, hide a domination that generates oligarchic power structures, poverty of imagination, decline of poetic sensibility, conversation and empathy, shallow obsession with digital gadgets, in sum, knowledge aversion (cf. Aschoff, 2018;Collin and Pedersen, 2015;Duff, 2016). What follows from this line of argumentation is that the task of a renewed hermeneutic social theory is twofold: to criticize and negate the anti-intellectual structures and corresponding knowledge-averse culture of the digital age; and to cultivate the poetic sensibility and and intellectual capacity to face an open universe and imagine one beyond usurpation of dominating value spheres.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have analyzed the emergent and recent literary history of the "Silicon Valley novel" (Even & Street, 2018), others underlined the role played by the cultural hegemony of the Silicon Valley's products in defining the idea of time, optimizing productivity and minimizing time wasting (Wajcman, 2018). A consistent group of critical scholars criticized the social impacts (Benner, 2003), labor divisions (Fuchs, 2014) and economic accumulation driven by "the Silicon Valley myth" warning about ongoing attempts to clone the Californian model around the world (Duff, 2016). While technical studies are still questioning whether the Silicon Valley model could be replicated in other areas (Cook & Joseph, 2001;Etzkowitz, 2011;Fung, Aminian & Tung, 2018;Henton & Held, 2013), empirical researches have already demonstrated that it has been already tested in East Asia (Klingler-Vidra, 2016); other scholars have also investigated the possibility to replicate the Silicon Valley model also in Europe (Aydalot & Keeble, 2018).…”
Section: State Of the Artmentioning
confidence: 99%
“…Several previous works have noted Silicon Valley's particular ideological blend of often left-leaning counter culture and its attachment to a hyper-capitalist form of libertarianism (e.g. Barbrook and Cameron 1996;Duff 2016;Levina 2017). Duff (2016) labels this particular combination of ideologies 'iCapitalism'.…”
Section: Situating the Inquirymentioning
confidence: 99%
“…And you should be able to access that information when it matters most --when there is still time to change your life, and the lives of those you love, for the better. (Holmes 2015) ix This narrative individualization of healthcare plays perfectly into the libertarian side of Silicon Valley's ideology -or its 'visceral antistatism' (Duff 2016(Duff , 1608. Healthcare is reduced to a purely individualist and self-entrepreneurial endeavour; an individualism enshrined in 23andMe's slogan of 'one incredible you'.…”
Section: Introducing the Disruptorsmentioning
confidence: 99%